Effect of big five personality dimensions on the academic performance of college students - Rani Bhattacharjee, Rita; Ramkumar, Alajingi (Frontiers in Psychology, 2025)
IntroductionPersonality plays a crucial role in shaping the behavior of college students, impacting their academic performance, career prospects, and social relationships. This study examined the influence of the big five personality dimensions on students’ academic performance, specifically their grade point average (GPA).MethodsA purposive sampling method was used to analyze 384 students (220 males and 164 females) aged between 16 and 21 years from different family backgrounds (joint and nuclear families). Data were collected and analyzed using Statistical Package of Social Science (SPSS), categorizing students based on their GPA (<7 and >7) and assessing their personality traits.ResultsStudents with high conscientiousness demonstrated significantly better academic performance than those with high openness, agreeableness, extroversion, or neuroticism. While openness, extroversion, and agreeableness showed similar results, neuroticism harmed GPA.DiscussionThese findings suggest that conscientiousness is a strong predictor of academic success, which is consistent with prior research on self-discipline and goal-setting. This study highlights the importance of personality traits in educational outcomes, which can be useful for academic counseling and student development programs.